LOCAL SOLUTION AND BLOW-UP FOR A NONLINEAR KIRCHHOFF'S SYSTEM - Quispe Méndez, Teófanes (2005)
We study the existence and blow-up of the local solution to the mixed problem for a nonlinear Kirchhoff's system.